Guaranteeing safety and efficiency in magistral pharmacy: a study on quality control practices (Research, Society and Development, 2024)
Pharmaceutical compounding plays a crucial role in the healthcare system, particularly by providing personalized medications for patients who cannot be treated with industrialized drugs. This study aims to review the quality control practices in pharmaceutical compounding, with a focus on Brazilian regulations, such as ANVISA resolutions (RDC nº 33/2000, nº 67/2007, and nº 301/2019). The research highlights the physicochemical and microbiological methods used to ensure the safety and efficacy of compounded medications, as well as the challenges faced by the sector, such as the lack of professional training, inadequate infrastructure, and the implementation of advanced technologies. The review also addresses emerging trends, such as digital traceability and process automation, pointing out pathways for sector modernization. Furthermore, it proposes measures to enhance quality control, such as continuous education, investment in research, and strengthening regulatory oversight. This study emphasizes the importance of quality control for patient safety and the sector's credibility.